DEVELOPMENT OF CANVA-BASED EDUCATIONAL GAMES ON INTRODUCTION TO FRUIT TYPES - Atikah, Cucu; Choziahtillah, Ziah; Fadlullah, Fadlullah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Education provides the brightness of human life to be more directed according to the development of science and technology. At present technology is the main thing used in the field of education, for example it is used in learning media in schools. The purpose of this development research is to develop an educational game about fruit types with the Canva application for early childhood. The method used is research and development (R&D) with a qualitative descriptive approach, namely explaining the steps for making learning media material for identifying fruit types with the Canva application in early childhood and using the ADDIE model (analysis, design, development, implementation, evaluation) there are 5 stages and research focus using 3 stages, namely analysis, design, and development. Learning media with the Canva application produce educational games that are interesting and provide a variety of colors in learning that have the potential to be good learning media used during face-to-face and virtual face-to-face learning with educational game learning content material for identifying fruit types with games which are divided into three categories, namely guess the type fruit according to the characteristics of the fruit listed, guess the type of fruit by choice, and complete the word name of the fruit.